Reporte de dieta del Periquito de Cara Amarilla (Forpus xanthops) en el Bosque Tropical Estacionalmente Seco del Marañón, Perú. - Roncal-Rabanal, M.R. (2020)
Field observation records of Forpus xanthops are documented. Between 2013 and 2018, eight observations show F. xanthops feeding in various places in the seasonally dry tropical forest of the Marañón (BTES-Marañón) in Cajamarca and Amazonas. These records show that some items in their diet are cactus species, such as Espostoa lanata (Kunth) Britton & Rose, Espostoa mirabilis F. Ritte, Armatocereus rauhii Backeb, the latter two species being endemic to Peru. Feeding records include also Parkinsonia praecox (Ruiz & Pav.) Hawkins, Eriotheca discolor (Kunth) A. Robyns, Ochroma pyramidale (Cav. ex Lam.) Urb. and the fruit species Spondias purpurea L. and Citrus sinensis (L .) Osbeck.